EFEKTIVITAS SENAM DIABETES TERHADAP PENURUNAN KADAR GLUKOSA DARAH PADA PENDERITA DIABETES MELITUS (DM) TIPE-2 DI PUSKESMAS KTK KOTA SOLOK - Centia Komalasari, Afridon (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Diabetes Mellitus (DM) is a group of metabolic diseases characterized byhyperglycemia that occurs due to insulin secretion abnormalities, insulin work or both.Most cases of Diabetes is Type 2 diabetes mellitus (DM) caused by heredity, obesity due tolifestyle that lived. Type 2 DM is usually found in people over the age of 40 years. WestSumatra Provinces is one of the provinces with the highest number of DM patients, andranked third with a total of 44,561 people. The number of DM patients was also increasedin the work area of Puskesmas KTK (Kampai Tabu Kerambil), as evidenced by thepreliminary study conducted in April 2016 based on the visit of type 2 DM patients for 4months at Community Health Center of KTK 72 people. In general, the management ofDM Type 2 consists of four pillars of education, medical nutrition therapy, physicalexercise, and pharmacological intervention. Gymnastics diabetes is a physical exercisedesigned according to age and physical status and is part of the treatment of diabetesmellitus. During physical exercise the muscles of the body, the heart system and thecirculation of blood and breathing are activated. Therefore, the body's metabolism, fluidbalance and electrolytes and acid-base must adjust. If physical exercise continues to beincreased then the source of energy and muscle glycogen decreases, then there will be theuse of blood glucose and free fatty acids.Key word: gymnastics diabetes, diabetes mellitus type-2, blood glucose level